Markers of intracellular energy supply under conditions of hypoxia in premature babies - O.S. Godovanets (Zaslavsky O.Yu., 2024)
Background. Premature birth is the main cause of morbidity and mortality in the neonatal period, with long-term consequences for the child's further psycho-physical development and health. Given the objective deterioration of the economic component and social instability during the hostilities in Ukraine, the birth rate is not expected to increase in the coming years. So, it is important to preserve the life and health of every newborn child. The well-being of the intrauterine environment and birth, morphological and functional maturity at birth are the basis for the child's postnatal adaptation. Perinatal hypoxia is a predictor of significant metabolic disorders at the subcellular, cellular, organ and systemic levels. This results in impaired adaptation in the neonatal period and a high risk of developing functional and chronic pathology in the future. The purpose of the study is to examine the features of intracellular energy exchange in perinatal pathology in preterm infants. This will facilitate the investigation of the underlying pathophysiological mechanisms of severe forms of diseases and provide justification for the introduction of additional laboratory markers of hypoxic inflammation in practical neonatology. Materials and methods. A clinical and laboratory examination was conducted on 68 preterm infants with a gestational age of 32-33/6 weeks who exhibited severe forms of perinatal pathology. The comparison group comprised 27 conditionally healthy children with a gestational age at birth of 34-36/6 weeks. The inclusion criteria were a gestational age at birth of 32-33/6 weeks and severe perinatal pathology. The exclusion criteria were as follows: a gestational age at birth of less than 32 weeks or above 37 weeks, congenital malformations, and neonatal sepsis. In addition to the conventional methods of clinical and laboratory examination of newborns, indicators of intracellular energy exchange were determined: glycerol-3-phosphate dehydrogenase (GPDH) (EC 1.1.99.5), succinate dehydrogenase (SDH) (EC 1.3.99.1) and NADH (nicotinamide adenine dinucleotide, reduced form) dehydrogenase (EC 1.6.5.3) in lymphocytes, lactate, pyruvate and the lactate/pyruvate ratio in blood serum. The values of SDH, GPDH and NADH were employed in order to calculate the aerobic respiration (AR) rate and electron transport chain (ETC) coefficient. The statistical processing of the study results was conducted using the software package Statistica (StatSoft Inc., USA, version 10). A Student's t-test was employed for the comparison of quantitative indicators with normal distribution, at a significance level of p < 0.05 and p < 0.001. The qualitative differences between the comparison groups were assessed with the MedCalc software package (Statistical Software Package for Biomedical Research, 2023, version 16.1). Results. The findings demonstrated significant alterations in energy exchange in preterm infants subjected to hypoxic conditions in the context of severe perinatal pathology. In particular, a reduction in pyruvate levels accompanied by an increase in the lactate/pyruvate ratio suggests an insufficient energy exchange and the dominance of anaerobic glycolysis. Additionally, alterations in the activity of mitochondrial respiratory chain enzymes, including a decline in GPDH, an increase in SDH, a decrease in NADH, and a reduction in the AR rate accompanied by an increase in the ETC coefficient, were observed. The results of statistical receiver operating characteristic analysis of the laboratory indicators of energy exchange demonstrated a satisfactory level of sensitivity and specificity suggesting the potential utility of these parameters in perinatal pathology in preterm infants. Conclusions. The use of laboratory indicators of energy exchange, along with the conventional methods for additional paraclinical examination, will facilitate the prompt rectification of therapeutic measures, thereby enhancing the efficacy of medical care for preterm infants. This is achieved by the realignment of oxygen therapy measures at the intensive care stage. Furthermore, it provides a scientific foundation for the search for pharmacotherapeutic agents to control mitochondrial respiration disorders in conditions of hypoxic damage to the body.